Can people with intellectual disabilities not be good employees? A survey on psychological capital of students with intellectual disabilities in secondary vocational schools - Yi, Zhang; Hock, Kway Eng (South Asian Journal of Social Sciences and Humanities, 2023)
People with intellectual disabilities are the most difficult to find employment among all types of disabilities. However, their successful employment is a very beneficial thing for both individuals and society. Secondary vocational students with intellectual disabilities are the most likely candidates to develop into employees with disabilities. Paying attention to their psychological capital is helpful to improve their invisible psychological quality and employability. In this study, students with intellectual disabilities in two special education schools in Zigong, Sichuan Province, China were selected as research objects. These students were surveyed using the adapted “Psychological Capital Questionnaire for Adolescent Students” (PCQAS). The results show that the overall psychological capital level of the students with intellectual disabilities is positive; ‘Hope’ scored highest of the four dimensions; There was no significant difference in all scores for gender; In terms of grade, freshman year students scored significantly lower on ‘Resilience’ than sophomore year students in high school. After discussion, the following conclusions are reached:1. It is feasible for secondary vocational students with intellectual disabilities to complete the psychological questionnaire on the premise of some adaptation of the questionnaire;2. The overall psychological capital level of secondary vocational students with intellectual disabilities is not so bad as imagined. With proper education and care, they can have good mental quality;3. Resilience is a quality that needs to be paid special attention to in the process of preparing for employment of secondary vocational students with intellectual disabilities;4. The cultivation of resilience quality should be carried out as soon as the new students entering school;5. Psychological intervention is an educational method that can be tried.
Keywords: Secondary vocational students with intellectual disabilities & psychological capital